Systems approach to document management - Assimakopoulos, Nikitas A.; Miaris, Alexandros; Sakellaris, Elias (Acta Europeana Systemica, 2020)
The scientific field of Document Management within companies and organizations is very important and in this paper is delivered a systemic approach in both theoretical and empirical level. The study consists of two stages; first is the theoretical analysis of document management and systems and second is the empirical approach by developing and implementing specific strategic and operational planning in a real document management project. In the first stage the definitions of Administration (Management) and Document and the approach the Document Management theories are analyzed. Subsequently, the concept of document management, highlighting the benefits and other elements which made it historically significant and operationally necessary are presented. In the second stage a specific document management project is presented aiming to create an electronic library using document management systems (DMS). Examples of working libraries are illustrated, using DMS in a national and international level. The strategic planning, SWOT & PESTEL analysis and the operational planning of the project is explained. Additionally, the project management plan follows, showing its four stages, study, design, implementation and delivery. Specifically in step two, the stakeholders of the project and their relationships with the using the Design and Control Systemic Methodology (DCSYM) are depicted and the implementation of the project through the development of dynamic simulation of an intelligible model using VENSIM software, representing the main production process followed by a detailed model presentation. The alternative design is projected, given that the project could not be completed with the characteristics given, followed by the development and implementation of the research. The aim here is the assumption of the projects’problems by the stakeholders contribution and the determination of them in the management structure level.